The legal system for the right of air easement In accordance with Syrian Civil Aviation Law No. 6 of 2004 (Damascus University Journal for legal sciences, 2025)
Achieving legal protection for air activity, which is mainly carried out by aircraft, led to work on establishing airports according to standard specifications under the Chicago Convention on International Civil Aviation, and its annexes, especially Appendix 14 thereof. Airports, as far as they were concerned with the necessity of securing protection outside the borders of the airport, because the plane, when landing or taking off, needs large areas of land surrounding the airport, in order to carry out its operation, and that is according to technical and technical foundations, with which I want to spare the airspace the dangers it faces, This led to regulate the air easement right on lands near airports by Civil Aviation Law No. 6 of 2004, although this disagreed with the rules on which real estate ownership is based and restricted, which finds justification in the search for the legal system for the air easement right, and a statement The implications for both the Syrian Civil Aviation Authority and the owner of the attached property.